Satellite RNAs interfere with the function of viral RNA silencing suppressors - Shen, Wan-Xia; Au, Phil Chi Khang; Shi, Bu-Jun; Smith, Neil A.; Dennis, Elizabeth S.; Guo, Hui-Shan; Zhou, Chang-Yong; Wang, Ming-Bo (Frontiers in Plant Science, 2015)
Viral satellite RNAs (satRNAs) are small subviral RNAs and depend on the helper virus for replication and spread. satRNAs can attenuate helper virus-induced symptoms, the mechanism of which remains unclear. Here, we show that two virus-encoded suppressors of RNA silencing (VSRs), Cucumber mosaic virus (CMV) 2b and Tombusvirus P19, suppress hairpin RNA (hpRNA)-induced silencing of a β-glucuronidase (GUS) gene in Nicotiana benthamiana. This suppression can be overcome by CMV Y-satellite RNA (Y-Sat) via the Y-Sat-derived small interfering RNAs (siRNAs), which bind to the VSRs and displace the bound hpGUS-derived siRNAs. We also show that microRNA target gene expression in N. tabacum was elevated by CMV infection, presumably due to function of the 2b VSR, but this upregulation of microRNA target genes was reversed in the presence of Y-Sat. These results suggest that satRNA infection minimizes the effect of VSRs on host siRNA and microRNA-directed silencing. Our results suggest that the high abundance of satRNA-derived siRNAs contributes to symptom attenuation by binding helper virus-encoded VSRs, minimizing the capacity of the VSRs to bind host siRNA and miRNA and interfere with their function.